Pengaruh Kegiatan Musyawarah Guru Mata Pelajaran (MGMP) Terhadap Peningkatan Kinerja dan Profesionalisme Guru: A Literature Review - Nurul Arafah S.; Suci Yuniati; Depriwana Rahmi; Annisah Kurniati (Populer: Jurnal Penelitian Mahasiswa, 2024)
MGMP serves as a forum within the educational domain that fosters collaboration and the exchange of ideas among educators. This platform affords teachers instructing similar subjects the opportunity to share experiences, teaching strategies, and instructional resources. Through the MGMP, educators can broaden their perspectives, enhance their competencies, and develop new skills to address various challenges encountered in the teaching-learning process. This study employs the Systematic Literature Review (SLR) method with the aim of investigating the impact of MGMP on teacher performance and professionalism. Data collection involves the identification and review of all articles with similar research topics. The articles used in this study comprise 10 national journal articles obtained from Google Scholar. Out of the 10 analyzed articles, 9 articles assert that MGMP can enhance teacher performance and professionalism, while 1 article suggests that MGMP has a negative impact on teacher performance and professionalism.